2012
DOI: 10.15288/jsad.2012.73.444
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Consistency in Associations Between Depressive Symptoms and Alcohol Use in Early Adolescence

Abstract: ABSTRACT. Objective: Despite frequent theorizing, prior literature on the association between depressive symptoms and alcohol use in adolescence has been inconsistent. Yet studies have varied widely with respect to age at assessments, time frame of prediction, and controls for comorbid conditions and demographic factors. The current study examined whether the associations between depressive symptoms and alcohol use were similar in valence and magnitude over a 4-year period in early adolescence. Method: A sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
59
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 58 publications
9
59
0
7
Order By: Relevance
“…In addition, the alcohol use variables used were categorical rather than quantitative and were derived in the current sample, making comparisons to other studies less straightforward. Both alcohol use and internalizing symptoms were based on self-reports, and previous work has suggested that the observed relationship between these phenotypes might vary across reporters (McCarty et al, 2012). ALSPAC participants are largely of European descent, and these results might not be generalizable to other ethnicities.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, the alcohol use variables used were categorical rather than quantitative and were derived in the current sample, making comparisons to other studies less straightforward. Both alcohol use and internalizing symptoms were based on self-reports, and previous work has suggested that the observed relationship between these phenotypes might vary across reporters (McCarty et al, 2012). ALSPAC participants are largely of European descent, and these results might not be generalizable to other ethnicities.…”
Section: Limitationsmentioning
confidence: 99%
“…Proposed mechanisms for this relationship include (1) neurophysiological changes induced by extended exposure to alcohol, which increase the risk of developing mood and anxiety disorders, and (2) using alcohol to alleviate mood or anxiety symptoms (i.e., the 'self-medication theory') (Bolton et al 2009;McCarty et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Early adolescent depression predicts levels of alcohol, tobacco and cannabis use amongst girls but not boys (Fleming et al, 2008;Marmorstein, 2010;Saraceno, Heron, Munafò, Craddock, & van den Bree, 2012). The association of depression and alcohol use appears stronger for younger adolescents than older adolescents (Arnold, Greco, Desmond, & Rotheram-Borus, 2014) and it is independent of the autoregressive effects for alcohol use, conduct disorder, academic achievement, and socioeconomic disadvantage (Fleming et al, 2008;Marmorstein, 2010;McCarty et al, 2012;Saraceno et al, 2012). In addition, certain anxiety disorders predict alcohol use over time Polydrug use and psychological distress 4 (Kaplow, Curran, Angold, & Costello, 2001), and, at least in older adolescents, these effects are significant after controlling for conduct disorder (Zimmermann et al, 2003).…”
mentioning
confidence: 99%